2011
DOI: 10.1093/ecam/nep166
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study on the Immunomodulatory Effects of Electroacupuncture in DNP‐KLH Immunized Mice

Abstract: This study was conducted to compare the effects of low frequency electroacupuncture (EA) and high frequency EA at acupoint ST36 on the production of IgE and Th1/Th2 cytokines in BALB/c mice that had been immunized with 2,4-dinitrophenylated keyhole limpet protein (DNP-KLH), as well as to investigate the difference in the immunomodulatory effects exerted by EA stimulations at acupoint ST36 and at a non-acupoint (tail). Female BALB/c mice were divided into seven groups: normal (no treatments), IM (immunization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…[85], individuals with allergic process is found high levels of immunoglobulin IgE, in response to environment allergens, in the same way that IL4. In 100% of the papers that used IgE as markers, the results found after the acupuncture went of reduction in the serum levels [26,29,52,53].In the same way found a coherence in the citations of other authors, white respect to decrease to IL4 after the acupuncture [26,42,52,63]. Such fact corroborates with a tendency for consensus that the acupuncture effect is immunomodulators in the allergic processes, being.…”
Section: Immunoglobulins (Ig)mentioning
confidence: 75%
See 2 more Smart Citations
“…[85], individuals with allergic process is found high levels of immunoglobulin IgE, in response to environment allergens, in the same way that IL4. In 100% of the papers that used IgE as markers, the results found after the acupuncture went of reduction in the serum levels [26,29,52,53].In the same way found a coherence in the citations of other authors, white respect to decrease to IL4 after the acupuncture [26,42,52,63]. Such fact corroborates with a tendency for consensus that the acupuncture effect is immunomodulators in the allergic processes, being.…”
Section: Immunoglobulins (Ig)mentioning
confidence: 75%
“…It can be seen by looking at Figure 2, the acupuncture point more tested in experimental studies in rats and humans was St 36 (Zusanli), together making a total of 39 articles (73.5%) of articles mentioning acupuncture points tested, and with animals, especially rats(14papers) and humans( 25papers).As related to the point ST36 with the population profiles found in animals, 48% with inflammation [16,18,23,26,30,39,41,46,48,54,59], 26% of post-surgical, trauma or stress induced by cold [21,31,34,38,56,57]), 13% with cancer [48,50,58], 9% with allergic processes [42,52] and only 4% of healthy individuals [35].However in humans, there were no highlights for either disease as an object of study, and found the use of St 36 in inflammation [63], cancer [47], allergic rhinitis [17,27,29], elderdy [19,65] and athletes [24], healthy [40],depression [64] In humans, the equivalence point with ST36 (Zusanli) appears LI4 (Hegu), with 14 and 12 papers respectively, and in 8 of these items, the points LI 4, and St36 are used simultaneously. In animals there was only one papers used LI 4 acupuncture point, separately, being expressed clearly in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 EA is used for analgesic effects or overcoming pain, relaxation, improving blood circulation, and overcoming muscle disorders, has an immuno modulatory effect by affecting the autonomic nervous system (ANS) and the hypothalamicpituitary adrenal (HPA) axis. 6,7 Based on the research, EA at point ST36, BL18 and BL20 can increase the percentage of lymphocytes that can increase the body's ability to fight cancer. 8 BC will stimulate cellular or humoral immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…5 Animal experiments show that EA stimuli can modulate the immune response. 7 Other research proves that EA can relieve pain in cancer, stimulate the body's immune function including increasing blood counts, increasing lymphocytes and increasing NK cell activity. 11 The effects of low frequency EA appear after 30 minutes and are adequate between 30 minutes and 45 minutes.…”
Section: Introductionmentioning
confidence: 99%